Provincial distribution and predictors of desire for more children among married and cohabiting women in Sierra Leone - Augustus Osborne (Discover Public Health, 2025)
Abstract Background Fertility rates in Sierra Leone remain high, with an average woman having around four children in her lifetime. This high fertility rate impacts population growth, straining resources like healthcare and education. It can also have consequences for women's health and well-being. This study, therefore, examined the desire for more children and its predictors among women in Sierra Leone. Methods The study analysed the 2019 Sierra Leone Demographic and Health Survey data. A total of 8,031 married and cohabiting women comprised the study. Mixed-effect regression analysis examined the predictors of the desire for more children. The regression results were presented using an adjusted odds ratio (aOR) with 95% confidence intervals (CI). Results The proportion of desire for more children was 68.4% [66.8, 70.0] among married and cohabiting women in Sierra Leone. Married and cohabiting women aged 25 and above had lower odds of desiring more children than those aged 15–19, with the lowest odds among those aged 40 + [aOR = 0.01; 95% CI 0.00, 0.02]. Married and cohabiting women with four or more children [aOR = 0.37; 95% CI: 0.26, 0.52] had lower odds of desiring more children than those with fewer than four children. Married and cohabiting women with 1–3 living children [aOR = 0.06; 95% CI: 0.02, 0.17] and 4 + living children [aOR = 0.01; 95% CI 0.00, 0.04] had lower odds of desiring more children than those without children. Married and cohabiting women who use contraceptives [aOR = 0.73; 95% CI 0.59, 0.90] had lower odds of desiring more children than those who don’t. Married and cohabiting women who use the internet [aOR = 1.61; 95% CI 1.07, 2.42] had higher odds of desiring more children than those who don’t. Married and cohabiting women with 4–5 ideal number of children [aOR = 1.80; 95% CI 1.27, 2.55] and 6 + ideal number of children [aOR = 5.26; 95% CI 3.65, 7.58] had higher odds for desiring more children than those with 0–3 ideal number of children. Married and cohabiting women living in the northern province [aOR = 1.85; 95% CI 1.23, 2.81] had higher odds of desiring more children than those living in the Eastern province. Conclusion The results suggest that fertility desires among married and cohabiting women in Sierra Leone are shaped by social, demographic, and behavioural contexts. The reduced desire for more children among older women and those with larger families highlights the importance of tailoring reproductive health services to meet the needs of different life stages and family sizes. The association between contraceptive use and lower fertility desires underscores the role of access to and education about contraception in shaping family planning decisions. Meanwhile, the higher fertility desires among women who use the internet or reside in the northern province point to potential cultural or informational influences, suggesting that targeted communication strategies could address provincial and behavioural variations in fertility preferences. .